Identify damage to the mixer motor on the banbury machine using the vibration method - Panca Purwanto; Subekti Subekti; Abdul Hamid; Nur Indah (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
The Banburyy mixer machine is a tool used to mix materials, such as raw rubber, carbon and chemicals into a homogeneous mixture. The Banburyy engine component consists of a rotor. The rotor rotates as a result of the power transmission coming from the industrial motor, the power transmission uses a gearbox. Therefore, induction motors play an important role in Banbury engines. If damage to the induction motor is not detected early, it can result in more severe damage or even unusability. Therefore, in this paper we will analyze the characteristics of bearing damage using the Fast Fourier Transform (FFT) method and the Hilbert method on mixer motors. The bearings used in the mixer motor are SKF 6330/C3 bearings in the drive end position and SKF 6324 types in the non-drive end motor position. The measurement results were then processed using the Fast Fourier Transform (FFT) and Hilbert Transform methods. The rotation speed variations carried out in the test were 500 rpm, 1000 rpm and 1500 rpm. Bearing damage analysis uses a vibration method that is obtained based on characteristic frequency values that indicate the occurrence of damage, in the form of Ball Spin Frequency (BSF) on the ball, Ball Pass Frequency Outer (BPFO) on the outer track, Fundamental Train Frequency (FTF) that occurs on the cage, and Ball Pass Frequency Inner (BPFI) on the inner track, according to bearing specifications and motor shaft rotational speed. From the analysis results, it was found that in the SKF 6330/C3 bearing an amplitude appeared at a frequency close to the FTF value of 7.031 Hz along with its harmonic frequencies, whereas in the SKF 6324 bearing no frequency of damage appeared. This indicates that the bearing in the drive end position, namely the SKF 6330/C3 bearing, is thought to have experienced damage to the cage bearing (ball bearing cage). The action taken is to replace the bearing with a new one as soon as possible